The emotional side of post-traumatic stress reaction during COVID-19 pandemic: an Italian survey - Gianluigi Ferrante; Pierre Gilbert Rossini; Stefano Rousset; Luca Ostacoli; Cristiano Piccinelli; Sara Carletto; Livia Giordano (BMC, 2022)
Abstract Background Social restrictions due to COVID-19 might have had a significant impact on mental health. The aim of this study was to assess the prevalence of four emotional domains (nervousness, anger, numbness, physiological arousal) in a sample of citizens during the first pandemic wave in 2020, and their association with sociodemographic characteristics, housing conditions and lifestyle modifications. Methods A cross-sectional study based on a self-administered online questionnaire was set up to investigate emotions. Respondents were recruited through a non-probabilistic snowball sampling approach. The SPAN questionnaire was used to measure emotions in the interviewed population. The association between emotions and independent variables (gender, age, marital status, educational level, working condition, housing condition, COVID-19 positivity, sleep disturbance, increase in alcohol consumption and decrease in physical activity) was assessed through the multivariate Poisson regression. Results A total of 6,675 subjects were included in the analysis. Almost half of respondents (48.9%) experienced nervousness, 41.3% anger, 15.6% numbness and 18.8% physiological arousal. Females were more likely to face nervousness, anger and physiological arousal. For all the outcomes a decreasing trend was observed from younger to older. Singles were more likely to experience numbness compared to married people. Increase in alcohol consumption was associated with nervousness, anger and numbness. Decrease in physical activity was associated with nervousness, anger and physiological arousal. Restless sleep was the variable most associated with all emotional domains. Conclusions The first COVID-19 pandemic wave had a significant emotional impact on this sample, especially among younger people, singles and females. Even without reaching clinical relevance, these emotions could represent a form of psychological distress, which requires the implementation of preventive strategies, in particular regarding lifestyle care.